2020
DOI: 10.1097/ncm.0000000000000485
|View full text |Cite
|
Sign up to set email alerts
|

Death and Grieving for Family Caregivers of Loved Ones With Life-Limiting Illnesses in the Era of COVID-19

Abstract: Purpose: Family caregivers of a loved one with a life-limiting or terminal illness are often overwhelmed by, and underprepared for, their responsibilities. They often need help from family members and friends to provide comprehensive care. When death occurs, funerals and other death-related rituals bring family and communities together to honor the life and mourn the death of a loved one and provide needed support to family and caregivers. These collective rituals are often deeply rooted in cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 11 publications
1
14
0
2
Order By: Relevance
“…This suggests that the COVID-19 pandemic has a significant impact on the grieving and caregiving process before a loss and represents another stress factor that should be considered in patient care. Therefore, this is the first study to confirm previous theoretical assumptions about the negative effect of the COVID-19 pandemic on the grieving process [ 19 , 20 ]. As COVID-19 related fears also emerged as a significant correlate for preparedness for death, it may further complicate preparation processes for the death of a loved one.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…This suggests that the COVID-19 pandemic has a significant impact on the grieving and caregiving process before a loss and represents another stress factor that should be considered in patient care. Therefore, this is the first study to confirm previous theoretical assumptions about the negative effect of the COVID-19 pandemic on the grieving process [ 19 , 20 ]. As COVID-19 related fears also emerged as a significant correlate for preparedness for death, it may further complicate preparation processes for the death of a loved one.…”
Section: Discussionsupporting
confidence: 67%
“…One example are COVID-19 related fears. While many studies assume negative effects of COVID-19 on the grieving process [ 19 ], studies investigating the effect of COVID-19 on bereavement mostly consist of expert opinions, commentaries or recommendations for research and practice, lacking of empirical studies [see 20 ]. Also, the individual prognosis of the loved ones may play a role in grieving and preparation processes [ 21 , 22 ], however, its relationship with pre-loss grief or preparedness has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…Studies [ 42 , 43 ] have shown that high self-efficacy can improve the quality of care and ultimately improve individual and organizational performance. Scholars [ 44 ] found that during the coronavirus disease-2019 (COVID-19) pandemic, an assessment by nurses found that the ward nurses experienced higher than normal levels of despair, social isolation, and physical symptoms due to grief. Japanese scholars found that only 27% of nurses performed palliative care family psychological support care [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Policies that mandate restricted family member visitation in acute care settings have been commonly enacted throughout the COVID-19 pandemic to help limit spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus, reduce use of personal protective equipment (PPE), and organize care [ 7 , 8 ]. These restrictions have been reported to result in consequences for patients and families alike, such as distress [ 9 ], grief [ 10 ], impaired coping [ 10 ], and reduced quality-of-life [ 11 ]. Restricted visitation policies have also been reported to impact mental health and well-being of healthcare professionals, including peritraumatic dissociation [ 12 ], moral distress (when one feels the ethically correct action is different from what one is doing) [ 13 , 14 ], burnout (exhaustion from excessive, prolonged stress and general stressors in the work environment), and compassion fatigue (triggered by continual use of empathy and emotional energy) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%